A Programmer's Introduction to CSharp 2.0 3rd Edition - Gunnerson, Eric (Apress, 2012)
Even before the first version of C# officially shipped, the C# language design team was getting feedback from customers. Overall, the feedback was positive, but developers were missing the flexibility of generic types (a facility also known as templates or parameterized types in some languages). This wasn’t a surprise to the design team; we would have liked to have had generics in the original release as well, but doing them the right way—as a .NET runtime feature, accessible to all languages—was something that wouldn’t fit into the schedule for v1.0, or even in the following v1.1 release.